Tantangan Dan Solusi Dalam Pengelolaan Arsip Di Era Digital - Tengku Darmansah; Agung Muhammad Nur; Hasbih Soleh Suryadi; Lucky Tirta Nurarfiansyah (CV. ITTC INDONESIA, 2024)
This research discusses archive management in the digital era in educational institutions through a library research approach. The main focus is identifying key issues such as challenges and solutions. The digital era has dramatically changed the landscape of records management. Advances in information and communications technology have brought new opportunities and challenges to organizational records management. The main challenges facing the digital era of records management include large amounts of data, the rate of information growth, the complexity of file formats, and the need for data security and integrity. This article reviews these challenges and introduces solutions you can implement to overcome them.